Molecular and epidemiologic study of Clostridium difficile reveals unusual heterogeneity in clinical strains circulating in different regions in Portugal. (August 2016) - Santos, A.; Isidro, J.; Silva, C.; Boaventura, L.; Diogo, J.; Faustino, A.; Toscano, C.; Oleastro, M.
Abstract: Clostridium difficile infection (CDI) represents a great healthcare burden in developed countries. The emergence of the epidemic PCR ribotype (RT) 027 and its acquired fluoroquinolones resistance have accentuated the need for an active surveillance of CDI. Here we report the first countrywide study of CDI in Portugal with the characterization of 498 C. difficile clinical isolates from 20 hospitals in four regions in Portugal regarding RT, virulence factors and antimicrobial susceptibility. We identified 96 RTs with marked variations between and within regions, as only six RTs appeared in all four regions. RT027 was the most frequent RT overall (18.5%) and among healthcare facility-associated isolates (19.6%), while RT014 was the most common among community-associated isolates (12%). The north showed a high RT diversity among isolates and a low moxifloxacin (MXF) resistance rate (11.9%), being the only region in which RT027 was not predominant. In contrast, the isolates from the centre presented the highest RT027 frequency, and 53.4% were resistant to MXF. Overall, MXF resistance (33.2%) was associated (p <0.001) with the presence of binary toxin genes and mutations in tcdC regardless of the RT. Both traits appeared in almost 30% of the strains. RT027 showed a reduced susceptibility to metronidazole (p <0.01), and RT126 had higher minimum inhibitory concentrations to vancomycin (p = 0.03) compared to other RTs. The present study highlights an unusual heterogeneity of RTs in Portugal, with a high frequency of hypervirulent RTs and the emergence of virulence factors in non-027 RTs, emphasizing the need for a surveillance system for CDI in Portugal.